Peran Bhabinkamtibmas dalam Melaksanakan Penyuluhan Pencegahan Pelecehan Seksual terhadap Anak - Leony, Nesia (Advances in Police Science Research Journal, 2020)
ABSTRACT This research is motivated by the rampant cases of sexual harassment of minors, which is increasing every year in the Lembang Police Sector. This is what makes the case of Child Sexual Abuse begin to be a concern and must be resolved. Handling from the rise of the case is to improve the role of Bhabinkamtibmas in the description of duties and responsibilities daily, control the implementation of Bhabinkamtibmas duties to be more directed, and refer to written rules and examine what factors influence the role of Bhabinkamtibmas in carrying out their duties. This research method was conducted with a qualitative approach. Using descriptive analysis research methods. Data collection techniques by interviewing, observing, and studying documents. Meanwhile, the validity and reliability of the research data using data triangulation techniques, using data analysis in the form of data reduction, data presentation, and drawing conclusions and verification Based on the results of the study showed that the implementation of the role of Bhabinkamtibmas was still incomplete analyzed with crime prevention theory and the concept of success of community policing, the theory of communication elements and Perkap Number 21 of 2007, as well as the influencing factors were analyzed with work efficiency theory. The inhibiting factors are the time of task implementation, motivation, and completeness of the facilities. The impact of the Bhabinkamtibmas is still less felt by the community because the target of the counseling is inaccurate, the material is still general, and has not been focused on sexual harassment still only on the appeal of kamtibmas. According to the results of research that has been obtained by the author, the authors provide advice to the Chief of Police, Kasat Binmas and Kapolsek as leaders to pay more attention to the role of Bhabinkamtibmas in understanding the tasks of the field of extension as well as paying attention to the problems of facilities and infrastructure needed, in addition to Bhabinkamtibmas to always improve their knowledge and ability to extension materials can be well received by the community.